2020
DOI: 10.3390/molecules26010137
|View full text |Cite
|
Sign up to set email alerts
|

Curative Effect of Catechin Isolated from Elaeagnus Umbellata Thunb. Berries for Diabetes and Related Complications in Streptozotocin-Induced Diabetic Rats Model

Abstract: In this study, catechin (CTN) isolated from Elaeagnus umbellata was evaluated for in vitro antioxidant potential and inhibition of carbohydrate digestive enzymes (α-amylase and α-glucosidase). The compound was also tested for its in vivo antidiabetic potential using Sprague-Dawley rats as experimental animals. The effects of various doses of catechin in STZ (Streptozotocin) induced diabetic rats on fasting blood glucose level, body weight, lipid parameters, hepatic enzymes, and renal functions were evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
6
26
0
Order By: Relevance
“…Percent DPPH inhibition activity in the pancreas of normal control group (75.55 ± 3.12) was significantly (### p < 0.001) high as compared to diabetic control group (22.41 ± 4.25). % DPPH inhibition activity of glibenclamide and morin (2,5,10,15,30, and 50 µg/kg body weight) treated groups in the pancreas tissues were 49.88 ± 3.21 **, 52.66 ± 2.81 **, 60.42 ± 2.12 ***, 65.33 ± 22.13 ***, 69.33 ± 3.12 ***, and 71.42 ± 3.23 *** which were significantly higher than that of diabetic control group.…”
Section: Effect Of Various Treatments On Intracellular Ros Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Percent DPPH inhibition activity in the pancreas of normal control group (75.55 ± 3.12) was significantly (### p < 0.001) high as compared to diabetic control group (22.41 ± 4.25). % DPPH inhibition activity of glibenclamide and morin (2,5,10,15,30, and 50 µg/kg body weight) treated groups in the pancreas tissues were 49.88 ± 3.21 **, 52.66 ± 2.81 **, 60.42 ± 2.12 ***, 65.33 ± 22.13 ***, 69.33 ± 3.12 ***, and 71.42 ± 3.23 *** which were significantly higher than that of diabetic control group.…”
Section: Effect Of Various Treatments On Intracellular Ros Levelmentioning
confidence: 99%
“…Antioxidants are bioactive compounds that regulate redox status by blocking or reducing the oxidation of substances like fats, oil, and foods. Numerous studies have shown that antioxidants like lycopene, retinol, α- and γ-tocopherol, β-cryptoxanthin, ascorbic acid, α- and β-carotene, and lutein are present in different plants, essentially reducing diabetes complications [ 9 , 10 , 11 ]. The tendency in screening the antidiabetic and hypoglycemic potential of medicinal plants has increased, as it provides an important source as they are a good candidate to isolate novel effective drugs for this chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that catechin significantly decreased the different lipid parameters, hepatic, and renal function enzyme levels along with HbA1c levels in diabetic rats while remarkably increased the high-density lipoprotein (HDL) levels with values comparable with the glibenclamide. Also, α -glucosidase and α -amylase inhibitory activity of catechin have been reported with inhibition percent of 80% and 79%, respectively [ 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…3.2.1.1) catalyze the hydrolysis of α -1,4 glycosidic bonds present in starch, glycogen and other related carbohydrates to low molecular weight products, such as glucose, maltose and maltotriose [ 4 , 5 , 6 , 7 , 8 ]. These enzymes are present in plants, animals and microorganisms [ 9 ] and have extensive applications in medicine [ 10 , 11 , 12 , 13 , 14 ], textiles [ 11 ], detergent [ 11 ], fermentation [ 11 ] and the food industry [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to industrial use, α -amylase from porcine pancreas is used for example in health food research [ 16 , 17 , 18 ], to assay resistant starch (RS), not broken down by human enzymes in the small intestine [ 19 ] and is also used in medical diagnostics [ 12 , 13 , 14 ]. One of the problems is effective diagnostic methods allowing for the prognosis of pancreatic cancer of cancer, which is an exceptionally aggressive tumour with high mortality.…”
Section: Introductionmentioning
confidence: 99%